Desain Sistem Vakum untuk Mendinginkan Ruang Transformator - Benny Dwika Leonanda; Yul Hizhar; Firman Ridwan; Diki Zuhury (Metal: Jurnal Sistem Mekanik dan Termal)
An analysis has been carried out on designing a 60 MVA 150 kV transformer cooling chamber vacuum system. The transformer cooling chamber is vacuumed up to a pressure of 0.001 kPa. This is done to avoid the formation of gas bubbles, avoid condensation and sterilize the transformer chamber before filling the coolant. Therefore, we need a vacuum pump and other equipment called a vacuum system. The analysis of the vacuum system includes the work required by the system, vacuum time, and electrical energy. The design wllii uses a rotary pump and a root pump by varying the number of pumps with two, three, and four pumps. The results of the analysis show that the work that must be done by the design is the largest and the vacuum time is the least in the design that uses 2 pumps with a value of 2860.38 Kj and 39.31 hours. While the effective electrical energy is found in a design that uses 3 pumps. It can be concluded that an effective design is found in the design using 3 pumps. From the tests carried out in the field for the design of 3 pumps there is a difference of 5.3 hours and 38.31 kWh compared to the theoretical test.